How to talk to a borderline - Lachkar, Joan (New York : Brunner-Routledge, 2010)
'In How to Talk to a Borderline, Joan Lachkar introduces Borderline Personality Disorder (BPD) and outlines the challenges and difficulties it presents to clinicians. She expands current understanding of BPD by outlining eight different kinds of borderline personality disorders and how each of these requires specific communication techniques and methods. Case examples are offered throughout the text and in some cases describe the kinds of partners borderlines attract. This book offers new approaches to communicating, working with, and treating borderline personality disorders while integrating more contemporary treatment methods'--Provided by publisher
(Publisher-supplied data) The Borderline: An Overview -- Theoretical Perspectives: Looking to our Founding Fathers -- The Pathological Borderline -- The Malignant Borderline -- The Depressive Borderline -- The Obsessive-Compulsive Borderline (the Pack Rat/the Addict) -- The Antisocial -- The Passive-Aggressive (The'Poor Me' Victim) -- The Histrionic Borderline -- The Cross-Cultural Borderline (Cross/Cultural Couples) -- Recapitulation and Closing Thoughts
Keywords: Borderline personality disorder; Communication; Professional-Patient Relations